WHY DO THEY TAKE ONLINE LOANS? (STUDY ON HIGHER STUDENTS IN EAST JAVA, INDONESIA) - Bima Setyo Nugroho (Journal of Applied Economics in Developing Countries, 2024)
This research analyzes the influence of lifestyle, advertising, and ease of access on interest in online loans which is moderated by consumer behavior. This research uses a quantitative method with an accidental sampling technique. The total research sample was 132 students. The statistical analysis used in this research is an approach using Structural Equation Modeling- Partial Least Square (SEM-PLS) with the help of SmartPLS 3.0 software. The results of this research show that lifestyle influences consumer behavior. Apart from that, advertising and ease of access also have a positive and significant effect on consumer behavior. Meanwhile, consumer behavior also has a positive and significant effect on online loan interest. Meanwhile, consumer behavior also moderates the relationship between lifestyle and online loans. Based on the research results, the theoretical implication of this research is that lifestyle, ease of access, and advertising can influence a person's consumptive lifestyle which can direct someone to online loans, so students must pay attention to spending for future needs, so that the dangerous impacts caused by online loans may decrease during the study period. Meanwhile, practically, this research can be used as input for students regarding their responsibilities in managing finances and create awareness to reduce consumer lifestyles which can lead them to online loans which have several negative impacts.